The politics of animal rights activism: A frame analysis of the 2019 national direct action. Issue 2 (1st November 2021) - Rojahn, Madeleine; Hawley, Erin
This article analyses news coverage of the 2019 animal rights direct action in Australia. A combination of frame and discourse analysis was applied to 39 news texts published between 1 April 2019 and 25 July 2019 across three news outlets ‐ the ABC, Hobart's Mercury and The Australian. Our analysis paid particular attention to the inclusion of sources, and we found that elite sources dominated the news coverage, resulting in a replication of the very power imbalance that the activists were struggling against. We also found that language choices resulted in the construction of the direct action as threatening, harmful and 'un-Australian'. Our study shows that Australian news coverage of animal rights activism often marginalizes activist viewpoints, promoting a sense of division rather than diversity. While it is relatively easy for animal rights activists in Australia to gain mainstream news attention, these activists face powerful ideological barriers when attempting to raise awareness of their cause because the news media tends to obscure rather than open the pathway to a constructive public discussion on the issue of animal welfare.